Which edge to work: The use of interpretation in short-term child psychotherapy: A systematic literature review with clinical illustrations - Lane, Helen (Auckland University of Technology, 2005)
This literature review examines the use of interpretation in short-term child psychotherapy. Interpretation is central to psychodynamic practice work and as such it is thought important to understand its principles and features to assist with applying its best edge. The method used is a modified systematic literature review and draws on a range of theory within the psychodynamic paradigm to understand this topic. Clinical work is also used to illustrate some of the issues that can arise in the application of interpretation in terms of its limits and possibilities within short-term child psychotherapy. Children are increasingly being offered short-term psychotherapy as a way of assisting them with psychological difficulties. It seems important to understand the potentially varied use of interpretation in this context to help with practice. Interpretation has similar principles that apply to both adult and child work. A general discussion of the features of a good interpretation is discussed with reference to the quality of the therapeutic relationship, the features in the client, the timing of the interpretation and the communication that occurs between the client and therapist. The principles of interpretation need to be adapted in short term work with children. The findings are that children require a strong positive therapeutic relationship to make use of interpretation. This relates to their stage of development where they are more dependent on adults, have different ways of understanding and communicating and have less developed egos to assist them when they become overwhelmed by internal forces. The therapist should also take into account the child’s family circumstances and their “safety” inside and outside therapy. It is necessary that the therapist try to understand children’s non verbal material and to at times interpret in other ways such as through the play. Interpretation with children must take account of their ability to assimilate language and what it is they require from the interpretation to assist them back to the path of ordinary development. The task of a child is not to help them know or understand as do adults. What emerges is, interpretation works alongside other aspects of the work and cannot move beyond the child’s capacity to assimilate and make use of the interpretation. It is possible to interpret in short-term therapy with children, but we must be aware that the complex underlying process of therapy cannot be bypassed, and change will continue to be a slow and difficult business. For this reason it may be that only a partial edge of the interpretation will be applied in short-term work because this is all that is required.
Keywords: Child psychotherapy; Psychoanalytic interpretation